2015
DOI: 10.1080/00223980.2014.992382
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Associations Between Empathy and Depression as Moderated by Emotion Dysregulation

Abstract: Empathic tendencies have been associated with interpersonal and psychological benefits, but empathy at extreme levels or in combination with certain personal characteristics may contribute to risk for depression. This study tested the moderating role of cognitive emotion regulation in depression's association with empathy using nonlinear models. Young adults (N = 304; 77% female; M = 19 years) completed measures of cognitive emotion regulation strategies, depression, and affective and cognitive empathy. Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 72 publications
11
89
2
1
Order By: Relevance
“…For example, Lockwood et al (2014) found that trait cognitive, but not affective, empathy was positively correlated with the self-reported use of reappraisal. Similarly, another study found that higher levels of trait perspective taking were associated with increased use of reappraisal (Tully et al, 2016).…”
Section: Studymentioning
confidence: 86%
See 2 more Smart Citations
“…For example, Lockwood et al (2014) found that trait cognitive, but not affective, empathy was positively correlated with the self-reported use of reappraisal. Similarly, another study found that higher levels of trait perspective taking were associated with increased use of reappraisal (Tully et al, 2016).…”
Section: Studymentioning
confidence: 86%
“…Most previous studies have focused upon the moderating effect of regulation on the association between empathy and different behavioural or clinical outcomes, such as sympathy/personal distress (Okun et al, 2000), prosocial behaviours (Lockwood et al, 2014), and depression (Tully et al, 2016). While not the key question addressed by such studies, they have provided some evidence of a direct relationship between component processes of empathy and emotion regulation.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lack of studies with long-term follow-ups and several measurement points, the direction of the relationship between compassion and depressive symptoms have remained largely unclear (Celikel et al, 2010;Cusi et al, 2011;Farmer et al, 2003;Schreiter et al, 2013;Tully et al, 2016). It has been previously suggested that depressive states may cause temporary changes in personality traits (Hirschfeld, 1999;Hur & Kim, 2009).…”
Section: Dispositional Compassion and Depressive Symptomsmentioning
confidence: 99%
“…Empathy is a complex and multi-dimensional concept (7,8) and can be measured in different ways. Self-rating (the assessment of empathy using standardized instru-ments completed by the individuals assessed), patientrating (the use of instruments given to patients to assess the empathy they experience among their caregivers) and observer rating (the use of standardized instruments by an observer to rate empathy in communications between healthcare team members and patients) are among these methods (9).…”
Section: Introductionmentioning
confidence: 99%